Challenges and Outcome of Infected Non Union of Bones using Masquelet Technique: A Case Series - Shivam Sahu; V Venkataram; Jomon De Joseph; KR Ganesh Krishnan (Journal of Clinical and Diagnostic Research)
Infected non union of bones poses a significant challenge for orthopaedic surgeons due to the complexity of the problem, which includes bone necrosis, segmental bone loss, sinus tract formation, fracture instability, and scar adhesion of soft tissues. Bone infections remain a prevalent complication following fracture fixation. Effective management involves a multi-step approach, including debridement, soft tissue reconstruction, and bone stabilisation. The induced membrane technique, a two-stage process, has been successfully used to treat bone defects in both the upper and lower extremities. Here, four cases of infected non union treated using the Masquelet technique at various locations are presented. This technique involves a two-stage approach, where an induced membrane forms around a cement spacer, leading to the successful resolution of infection and bone union. Challenges encountered in these cases included recalcitrant infection, complex deformities, sclerotic bone ends, large bone gaps, shortening, and joint stiffness. Co-morbid factors such as smoking, diabetes, and hypovitaminosis D also influenced treatment choices and duration. All four cases treated with the Masquelet technique showed successful resolution of osteomyelitis, osseous union, and improvement in functional outcomes. Follow-up assessments revealed an average Visual Analogue Scale (VAS) improvement from 30 to 7.5, complete eradication of infection, and an average Lawton-Brody instrumental activities of daily living scale improvement from 13/23 to 21/23, with complete union of bone achieved in all four cases. Hence, it was concluded that the Masquelet technique is an effective approach for treating infected non union of bones, leading to the successful resolution of infection and bone union. Patience and perseverance are essential for achieving optimal outcomes.